2018
DOI: 10.1177/0300060517754025
|View full text |Cite
|
Sign up to set email alerts
|

Conservative laparoscopic management of adnexal torsion based on a 17-year follow-up experience

Abstract: Laparoscopic unwinding of adnexal torsion has been proposed for decades. However, this technique is still controversial regarding the concern of thromboembolic events. We present two cases of conservative laparoscopic management of adnexal torsion. In the first case, a 16-year-old adolescent with serous cystadenoma was successfully managed by untwisting and cystectomy. We followed up this patient for 17 years with regular re-examinations in our hospital. To the best of our knowledge, this is the longest follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
1
13
0
4
Order By: Relevance
“…Our study may also indirectly support ovarian preservation even in the setting of a necrotic‐appearing ovary given the fact that conservative surgery was not associated with perioperative complications. While our results are consistent with previous small studies that demonstrate no increase in complications following conservative surgery as compared with oophorectomy even with necrotic‐appearing ovaries, these observational data need to be followed by randomised prospective studies, especially to confirm the safety and utility of leaving necrotic‐appearing ovaries in situ following torsion …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study may also indirectly support ovarian preservation even in the setting of a necrotic‐appearing ovary given the fact that conservative surgery was not associated with perioperative complications. While our results are consistent with previous small studies that demonstrate no increase in complications following conservative surgery as compared with oophorectomy even with necrotic‐appearing ovaries, these observational data need to be followed by randomised prospective studies, especially to confirm the safety and utility of leaving necrotic‐appearing ovaries in situ following torsion …”
Section: Discussionsupporting
confidence: 90%
“…Studies have suggested no significant increase in complications with conservative surgery for ovarian torsion, although existing evidence is based on few studies with limited sample size . Practice patterns in the treatment of ovarian torsion are also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While our results are consistent with previous small studies that demonstrate no increase in complications following conservative surgery as compared with oophorectomy even with necrotic-appearing ovaries, these observational data need to be followed by randomised prospective studies, especially to confirm the safety and utility of leaving necrotic-appearing ovaries in situ following torsion. 8,13,15,17,23…”
Section: Interpretationsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Studies have suggested no significant increase in complications with conservative surgery for ovarian torsion, although existing evidence is based on few studies with limited sample size. 12,[15][16][17] Practice patterns in the treatment of ovarian torsion are also unknown. An understanding of current practice patterns in the USA and the incidence of perioperative complications is crucial to influence individual surgeon decision-making, set quality standards, fuel specialty-wide initiatives aimed at practice change and identify specific target populations that warrant attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have demonstrated ovarian preservation of function in 88–100% of cases of human torsion [ 4 ]. Other reports of ovarian function despite apparently ischemic-hemorrhagic appearance of torsed adnexa have been documented, favoring de-torsion rather than removal of the adnexa [ 9 ]. Several authors have demonstrated no difference in antral follicle count in small numbers of patients who underwent conservative detorsion of adnexa [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%